Strategi Peningkatan Kewirausahaan Santri Dalam Menghadapi Abad 21 - Erly Juliyani (Jurnal Multidisiplin Indonesia, 2024)
Entrepreneurship is becoming increasingly important for students, especially in adapting to the challenges and opportunities presented by the 21st century. Entrepreneurship skills not only help students in creating jobs, but also prepare them to innovate and compete in an increasingly complex global market. The method in this research is a literature study approach that involves analyzing literature and reliable sources to identify current trends in entrepreneurship education as well as best practices that can be applied in the santri environment. The results of the research are first, santri entrepreneurship training is conducted to improve the practical skills and knowledge of santri in managing businesses, so that they can be better prepared to face challenges in the competitive business world. Second, the field work practice of santri entrepreneurship in this context is a program designed to provide direct experience to santri in running a business, so that they can apply the knowledge gained in class to real situations. Third, The strategy of increasing santri entrepreneurship in facing the 21st century is carried out by developing a comprehensive training program, including technical skills and soft skills needed for success in the modern business world.